Expanding diversity of tick-borne phleboviruses (Phlebovirus mukawaense, Mudanjiang phlebovirus, Gomselga Virus, and Onega tick phlebovirus) in Russia - Mikhail Y. Kartashov; Valentina Y. Kurushina; Alexey O. Yanshin; Alina S. Zheleznova; Kirill A. Svirin; Tatyana V. Tregubchak; Vladimir A. Ternovoi; Alexander P. Agafonov; Anastasia V. Gladysheva (PLoS ONE, 2026)
Tick-borne phleboviruses represent emerging pathogens with zoonotic potential, yet their distribution across Asian Russia remains poorly characterized. This study investigated the prevalence, genetic diversity, and evolutionary dynamics of phleboviruses in 1,078 individual Ixodes persulcatus ticks collected from 143 locations across Asian Russia during summer 2023. Samples underwent PCR screening, high-throughput sequencing for genome reconstruction, phylogenetic analysis, and AlphaFold protein structural modeling. We detected 27 phleboviral isolates belonging to Phlebovirus mukawaense (MKWV), Mudanjiang phlebovirus, Onega tick phlebovirus, and Gomselga virus , with prevalence rates of 0.6%, 0.1%, 0.3%, and 1.5%, respectively. Phylogenetic analysis suggested Gomselga virus belongs within the MKWV species complex. Complete coding sequences of Russian MKWV isolates enabled high-confidence structural predictions for key proteins. The predicted tertiary structure of the MKWV nucleoprotein exhibits strong similarity to those of Rift Valley fever virus and Toscana virus, despite limited sequence identity. The MKWV nucleoprotein features a conserved globular core with a well-defined RNA-binding cleft. Segment-specific phylogenetic incongruence among Primorsky MKWV isolates indicated potential reassortment events. Additionally, coinfections involving MKWV and Alongshan virus, Borrelia miyamotoi , or Rickettsia spp. were identified. These findings significantly expand the known geographic range and genetic diversity of tick-borne phleboviruses in Russia. The integration of genomic and structural data provides a robust framework for functional annotation and highlights the evolutionary stability of essential viral domains. Further research should focus on virus isolation and investigating antigenic properties and replication capacity in mammalian cells.